Structure-Function Relationships With Spectral-Domain Optical Coherence Tomography Retinal Nerve Fiber Layer and Optic Nerve Head Measurements - Pollet-Villard, Frédéric; Chiquet, Christophe; Romanet, Jean-Paul; Noel, Christian; Aptel, Florent (Investigative ophthalmology & visual science, 2014)
To evaluate the regional structure-function relationship between visual field sensitivity and retinal nerve fiber layer (RNFL) thickness and optic nerve head (ONH) measurements using spectral-domain optical coherence tomography (SD-OCT). Prospective cross-sectional study conducted on patients with glaucoma, suspected glaucoma, and healthy subjects. Eyes were tested on Cirrus OCT and standard achromatic perimetry. RNFL thickness of 12 peripapillary 30° sectors, neuroretinal rim thickness extracted from 36 neuroretinal rim scans, and Bruch membrane opening minimum rim width (BMO-MRW)-a recently defined parameter-extracted from 36 neuroretinal rim scans were obtained. Correlations between peripapillary RNFL thickness, neuroretinal rim thickness, all six sectors of BMO-MRW, and visual field sensitivity in the six corresponding areas were evaluated using logarithmic regression analysis. Receiver operating curve areas were calculated for each RNFL, ONH, and macular ganglion cell analysis parameter. We included 142 eyes of 142 subjects. The correlations (r(2)) between RNFL thickness, Cirrus-based neuroretinal rim thickness, BMO-MRW and visual field sensitivity ranged from 0.07 to 0.60, 0.15 to 0.49, and 0.24 to 0.66, respectively. The structure-function correlations were stronger with BMO-MRW than with Cirrus-based neuroretinal rim thickness. The largest areas under the receiver operating curve were seen for rim area (0.926 [95% confidence interval 0.875, 0.977]; P < 0.001) in eyes with glaucoma and for average RNFL (0.863 [0.769, 0.957]; P < 0.01) in eyes with suspected glaucoma. The structure-function relationship was significantly stronger with BMO-MRW than other ONH SD-OCT parameters. The best diagnostic capabilities were seen with rim area and average RNFL.